Оцінка вкладу до господарського товариства - Ханієва, Фатіма Магомедівна; Ханиева, Фатима Магомедовна; Khaniieva, Fatima M. (My University, 2017)
У цій статті автор розглядає порядок оцінки негрошових вкладів та проводить теоретичний аналіз чинних законодавчих положень з приводу розглядуваного питання. Крім того, наводяться наукові визначення грошової оцінки вкладів залежно від виду організаційноправової форми господарського товариства. Також дослідник виявляє необхідність нормативного визначення критеріїв такої оцінки, способів її фіксації, висуває пропозиції для можливих законодавчих змін чинного українського законодавства з опором на зарубіжний досвід.

В этой статье автор рассматривает порядок оценки неденежных вкладов и проводит теоретический анализ действующих законодательных положений по рассматриваемому вопросу. Кроме того, им даются научные определения денежной оценки вкладов в зависимости от вида организационно-правовой формы хозяйственного общества. Исследователь устанавливает необходимость нормативного определения критериев такой оценки, способов ее фиксации, а также выдвигает предложения для возможных законодательных изменений с учётом зарубежного опыта.

This article deals with the consideration of the procedure for evaluating capital contributions and theoretical analysis of the existing legislative norms about this question. Besides, the researcher gives the scientific definitions of the monetary valuation of contributions, depending on the organizational and legal forms of commercial companies. Also author discovers the necessity of a normative definition the criteria for such evaluation of a contribution, ways to hold and puts forward proposals for possible legislative changes, taking into account international experience. At the same time, attention is paid to evaluation of the capital contributions only by professional valuators and to fixation the evaluated contributions in the statutory documents. From the basic criteria the author proposes legislate such of them as justice, objectiveness, conscientious, reasonableness. This approach to the process of evaluation of the capital contributions is very perspective on the way of protecting the rights and interests of commercial company’s founders/members both during the period of establishment the company and in the future. As the result of this research, author proposes to amend the part 2 of Article 115 of the Civil Code of Ukraine, the part 2 of Article 86 of the Economic Code of Ukraine, the part 2 of Article 13 of the Law of Ukraine «On Commercial Companies», according to determined important theses.
Ханієва Ф. М. Оцінка вкладу до господарського товариства / Ф. М. Ханієва // Часопис цивілістики. – 2017. – Вип. 22. – С. 88-93.
Keywords: господарське товариство; статутний (складений) капітал; вклад; внесок; частка; порядок формування статутного (складеного) капіталу; оцінка вкладу; хозяйственное общество; уставный (складочный) капитал; вклад; взнос; доля; порядок формирования уставного (складочного) капитала; оценка вклада; commercial company; authorized (share) capital; capital contribution; share; the procedure for mak- ing a capital contribution; evaluation of contribution to a commercial company